Groundwater mixing and mineralization processes in a mountain–oasis–desert basin, northwest China: hydrogeochemistry and environmental tracer indicators - Ma, Bin; Jin, Menggui; Liang, Xing; Li, Jing (Hydrogeology journal, 2018)
Hydrogeochemistry and environmental tracers ( 2 H, 18 O, 87 Sr/ 86 Sr) in precipitation, river and reservoir water, and groundwater have been used to determine groundwater recharge sources, and to identify mixing characteristics and mineralization processes in the Manas River Basin (MRB), which is a typical mountain–oasis–desert ecosystem in arid northwest China. The oasis component is artificial (irrigation). Groundwater with enriched stable isotope content originates from local precipitation and surface-water leakage in the piedmont alluvial–oasis plain. Groundwater with more depleted isotopes in the north oasis plain and desert is recharged by lateral flow from the adjacent mountains, for which recharge is associated with high altitude and/or paleo-water infiltrating during a period of much colder climate. Little evaporation and isotope exchange between groundwater and rock and soil minerals occurred in the mountain, piedmont and oasis plain. Groundwater δ 2 H and δ 18 O values show more homogeneous values along the groundwater flow direction and with well depths, indicating inter-aquifer mixing processes. A regional contrast of groundwater allows the 87 Sr/ 86 Sr ratios and δ 18 O values to be useful in a combination with Cl, Na, Mg, Ca and Sr concentrations to distinguish the groundwater mixing characteristics. Two main processes are identified: groundwater lateral-flow mixing and river leakage in the piedmont alluvial–oasis plain, and vertical mixing in the north oasis plain and the desert. The 87 Sr/ 86 Sr ratios and selected ion ratios reveal that carbonate dissolution and mixing with silicate from the southern mountain area are primarily controlling the strontium isotope hydrogeochemistry.